Answer: a = -1 x = -3
Since the value of the function y = ax ^ 2 is -9, then y = -9; Since y = -9, then ax ^ 2 = -9 Next, we perform the usual calculation of the value “a”. It turns out: a = -9 / x ^ 2 Substitute the value x = -3 into the resulting equation. It turns out: a = -9 / (-3) ^ 2 Next, we make standard calculations. Do not forget that when raising a negative value to an even power, a positive value is obtained. It turns out: a = -9 / 9 And the answer: a = -1
One of the components of a person's success in our time is receiving modern high-quality education, mastering the knowledge, skills and abilities necessary for life in society. A person today needs to study almost all his life, mastering everything new and new, acquiring the necessary professional qualities.